2006
DOI: 10.3748/wjg.v12.i24.3906
|View full text |Cite
|
Sign up to set email alerts
|

How much helpful is the capsule endoscopy for the diagnosis of small bowel lesions

Abstract: In our relatively small series, we found that capsule endoscopy is a useful diagnostic tool particularly in diagnosis of obscure gastrointestinal bleeding, chronic diarrhea and in estimating the extension of Crohn's disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 34 publications
1
19
0
4
Order By: Relevance
“…CE facilitates effective decision-making regarding subsequent investigations and treatments [4] . Diagnostic yield of CE for OGIB varied between 31% and 91% [9,[17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] . Lema and Ruano-Ravina [32] reviewed the published studies of CE for OGIB and reported that sensitivity ranged from 79% to 95% and specificity from 75% to 100%.…”
Section: Indicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…CE facilitates effective decision-making regarding subsequent investigations and treatments [4] . Diagnostic yield of CE for OGIB varied between 31% and 91% [9,[17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] . Lema and Ruano-Ravina [32] reviewed the published studies of CE for OGIB and reported that sensitivity ranged from 79% to 95% and specificity from 75% to 100%.…”
Section: Indicationsmentioning
confidence: 99%
“…Recent studies showed the superiority of CE over conventional methods, but passive features such as inability to insufflate the bowel and to biopsy and lack of therapeutic capability have generated a debate on its advantages [6][7][8][9][10][11][12][13][14] . Newly developed balloon assisted enteroscopes are also available and have the potential to outscore CE in terms of diagnostic indications and therapeutic applications.…”
Section: Introductionmentioning
confidence: 99%
“…10 Our study evaluated CE findings in only one patient which had abnormal findings of nodular lesions in duodenum which was later confirmed as Brunner's gland hyperplasia and suspected submucosal bulge in the terminal ileum which could not be further evaluated. Due to the lack of sufficient cases, the role of CE in our study for the evaluation chronic unexplained abdominal pain could not be established the main drawback of our study was that the abnormalities detected on CE could not be confirmed due to the lack of double/single balloon enteroscopy in our center.…”
Section: Discussionmentioning
confidence: 92%
“…CE plays an important role in diagnosis of the small bowel diseases [16][17][18] , such as bleeding [19][20][21] , Crohn's disease [21][22][23] , tumors [20] , angioectasia [20] , etc. With the bowel peristalsis, CE passes through the small intestines and takes pictures of the intestinal cavity, though the total number of the images in each patient can vary from 40 000 to 60 000, with a median of 50 000, and the definite pv: Predictive value.…”
Section: Discussionmentioning
confidence: 99%